Psychometric evaluation of the health-seeking behavior scale based on Kroeger’s model for elective cardiac interventions - Afkar, Mehdi; Ostovar, Afshin; Tahmasebi, Rahim; Pourbehi, Mohammadreza; Omranikhoo, Habib; Amiri, Mohammad; Noroozi, Azita (Social Determinants of Health, 2020)
Background: Coronary artery bypass graft surgery (CABG) is one of the two most commonly used interventions for Myocardial Reperfusion. Studies suggest that the existence and direction of the effect of the factors affecting health-seeking behavior depend on the context of each society. Thus, this study aimed to introduce and validate a tool for investigating the factors affecting the health-seeking behavior of patients requiring a cardiovascular intervention as a prerequisite for planning and policymaking. Methods: By reviewing the literature and questionnaires previously used in the field of health-seeking behavior and the patient's decision-making process, a set of related questions was collected based on Kroeger’s model variables. Ten content experts were requested to evaluate each item and then content validity ratio (CVR) and content validity index (CVI) were calculated and used for instrument modification. Participants were included through a convenience sampling procedure. Exploratory factor analysis (EFA) and Confirmatory factor analysis (CFA) was used to assess construct validity. Cronbach's alpha coefficient was used to measure instrument reliability. Results: Of the 142 participants, 79 (55.5%) were male. Through the validation process, a hierarchical model with four factors and 20 items with three error covariance (accounting for 63.06 present of outcome variable variation) was confirmed. Also, an examination of the four constructs obtained with Cronbach's alpha coefficient was more than 0.8 indicating acceptable reliability. Conclusion: Findings suggest that the designed scale of health-seeking behavior based on Kroeger’s model is a reliable and valid scale among the Iranian population.